Evaluation of Garden Pea (Pisum sativum var. hortense L.) Genotypes Under Irrigated and Rainfed Condition Under Foothills of Terai Agro-ecological Region of West Bengal - V. C, Yathish; Chowdhury, Riman Saha; Datta, Suchand (International Journal of Bio-resource and Stress Management, 2021)
The experiment was carried out to study the performance of garden pea genotypes for growth, yield and quality during rabi season (November to april) of 2017–18 and 2018–19 with the help of split plot design through three number of replications. The results of the study revealed that, early flowering, flowering at early node and days to first harvest was earlier by 2.32, 2.90 and 0.89 days, respectively in rainfed conditions. Yield parameters like individual plant yield, number of pods plant-1, individual pod weight and total fresh yield were significantly reduced by water stress condition. Number of nodules plant-1 (7.93) and nodule dry weight (97.01 g) decreased in rainfed conditions, whereas root length (22.33 cm) was higher in rainfed condition. Considering yield, benefit cost ratio and moisture stress tolerance of garden pea genotypes, TSS content of fresh seeds was higher in rainfed conditions. Quality parameters such as protein content and shelling percentage were higher in irrigated conditions. Ascorbic acid content remained unchanged under both growing conditions. The varieties such as Arka Apoorva, Arka Priya, Goldie and GS-10 may be selected for cultivation under both irrigated and rainfed conditions. On the basis of per se performance and drought tolerant indices Arka Apoorva, Arka Priya and Jindal-10 may be selected as suitable for growing under moisture stress condition in terai agro-ecological condition of West Bengal.